Avoiding Covert Polygamy at the Office of Religious Affairs: Authority and Family Law Reform in the Prohibition of Marriage During a Wife's ‘Iddah Period - Dri Santoso; Zezen Zainul Ali; Siti Wahyuni (al-'adalah, 2025)
This study examines regulations prohibiting remarriage during the wife's waiting period (‘iddah) by examining the state's authority in regulating marriage and how legal development is carried out. The term waiting period (‘iddah) is commonly associated with women, but contemporary developments have introduced regulations stipulating that men also have a waiting period, specifically a prohibition on husbands marrying during their wives' ‘iddah, as outlined in the Circular Letter of the Directorate General of Islamic Community Guidance. This empirical research was conducted at the Office of Religious Affairs (KUA) in Metro City, Indonesia, using a socio-legal approach. Data were obtained through interviews with five KUA heads and relevant literature, then analyzed using Khaled Abou Fadl's theory of authority and Mochtar Kusumaatmaja's theory of development law. Research findings show that regulations prohibiting husbands from remarrying during their wives' waiting period are a renewal of Islamic family law in Indonesia, based on the principles of justice, equality, and legal benefit, particularly in avoiding covert polygamy. Second, this regulation is a manifestation of the state's coercive authority, which relies on its structural position in regulating and directing marriage law, including interpreting and translating Islamic normative values into regulations. This policy is a form of legal development as a control tool to protect a just society. The contribution of this research lies in its integrative approach to combining classical fiqh norms with the study of state policy authority in contemporary Islamic family law reforms.